Reduction of nutrients concentration in culture medium has no effect on bovine embryo production, pregnancy and birth rates - Ligiane de Oliveira Leme; Mauricio Machaim Franco; Otávio Augusto de Faria; Alexandre Rodrigues Caetano; Juliana Gonçalves de Souza; Luciano de Rezende Carvalheira; Emivaldo de Siqueira Filho; Margot Alves Nunes Dode (Scientific Reports, 2025)
Abstract To improve the quality of in vitro produced (IVP) embryos and reduce pregnancy losses, we proposed to reduce the components of the synthetic oviduct fluid (SOF) medium by 0% (SOF100), 50% (SOF50), and 75% (SOF25). First, embryos produced under these three treatments were evaluated for production, quality, lipid content, gene expression, and methylation patterns. The results indicated that all parameters analyzed were similar across all treatments (P > 0.05), suggesting that reducing media components does not affect embryo development and quality. Subsequently, we selected SOF25 for comparison with SOF100 in a commercial laboratory setting, evaluating embryo production, response to cryopreservation, gestation rate, and offspring birth. The data demonstrated that a 75% reduction in SOF medium components did not affect embryo development, quality, pregnancy rate, embryonic losses between 30 and 60 days, or birth rate (P > 0.05). To our knowledge, this is the first report on the pregnancy and birth rates of bovine blastocysts produced in media with nutrient concentrations as low as 25%. These results introduce novel cultural conditions that can be immediately incorporated into the IVF routine.